A conductive film electrode and its preparation method and application

By filling semiconductor nanoparticles in the catalyst layer of the alkaline electrolytic water film electrode to form a PN heterojunction, the problem of poor conductivity of the catalyst is solved, and the electrolytic efficiency is improved, making it close to the performance of noble metal catalysts.

CN117926314BActive Publication Date: 2025-03-28GUONENG SCIENTIFIC & TECHNOLOGICAL ACHIEVEMENTS TRANSFORMATION (BEIJING) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310805090.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-03-28
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The electrolytic efficiency of existing alkaline hydrolytic membrane electrodes is low, mainly due to the poor conductivity of the catalyst and the non-conductivity of the binder, resulting in low catalyst utilization.

Method used

Semiconductor nanoparticles are filled between the anode catalyst layer and the catalyst of the cathode catalyst layer to form a PN heterojunction to achieve electrocatalytic conduction of the catalyst and the semiconductor nanoparticles.

Benefits of technology

By improving the utilization rate of the catalyst and the overall catalytic efficiency, the electrolytic efficiency of the alkaline electrolytic water membrane electrode is significantly improved, making it close to the performance of noble metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117926314B_ABST
    Figure CN117926314B_ABST
Patent Text Reader

Abstract

The present invention provides a conductive membrane electrode and a preparation method and application thereof, comprising an anode catalyst layer and a cathode catalyst layer, wherein the gaps between the oxygen evolution catalyst in the anode catalyst layer and / or the hydrogen evolution catalyst in the cathode catalyst layer are filled with semiconductor nanoparticles, and a PN heterojunction is formed between the semiconductor nanoparticles and the semiconductor nanoparticles can be electrically catalytically connected with the oxygen evolution catalyst or the hydrogen evolution catalyst. The gaps between the catalysts in the conductive membrane electrode of the present invention are filled with semiconductor nanoparticles, and the semiconductor nanoparticles are fully contacted to form a PN heterojunction. The semiconductor nanoparticles can be electrically connected with the catalyst through electrocatalytic electrons, and the catalyst coated with a binder can also undergo a catalytic reaction, thereby improving the utilization rate of the catalyst, fully reacting the catalytic reaction, and effectively improving the electrolysis efficiency of the membrane electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogen production by alkaline water electrolysis, and in particular, relates to a conductive film electrode and a preparation method and application thereof. Background Art

[0002] At present, the mainstream water electrolysis hydrogen production technologies include alkaline water electrolysis (ALK), proton exchange membrane electrolysis (PEM), high-temperature solid oxide electrolysis (SOEC) and solid polymer anion exchange membrane electrolysis (AEM). Among them, alkaline water electrolysis hydrogen production technology was commercialized the earliest and has a relatively mature industrial chain. Although the efficiency of alkaline electrolysis technology is relatively low, its anode and cathode electrode plates do not contain precious metals, so the cost of the electrolyzer is relatively low and it is still widely used. Since the alkali solution concentration used in the alkaline water electrolysis electrolyzer is about 20-35wt%, the operating temperature range is 60-120℃, and the electrolysis environment of high temperature, strong alkali corrosion and electrochemical oxidation cannot use high-efficiency conductive agents such as conductive carbon. Therefore, the catalysts currently used to prepare alkaline water electrolysis membrane electrodes have poor conductivity and the electrolysis efficiency of alkaline water electrolysis membrane electrodes is low. For this reason, people have conducted a lot of research on how to improve the activity of catalysts.

[0003] Chinese patent ZL202080020021.3 provides an anode for alkaline water electrolysis, which comprises: a conductive substrate, the surface of which contains nickel or a nickel-based alloy; an intermediate layer, which is formed on the surface of the conductive substrate and contains a composition formula LixNi 2-x A lithium-containing nickel oxide represented by O2, wherein 0.02≤x≤0.5; and a catalyst layer formed on the surface of the intermediate layer and comprising a mixed cobalt hydroxide nanosheet Co-NS of a complex of a metal hydroxide and an organic substance. The electrolysis performance of the anode for alkaline water electrolysis is not easily deteriorated during the electrolysis operation, and the excellent catalytic activity can be stably maintained for a long time.

[0004] Chinese patent application 202211630906.2 discloses a water electrolysis oxygen evolution catalyst, which is a spherical catalyst containing nickel and iron, and the surface of the spherical catalyst has a porous structure with nanoscale pores, wherein the molar ratio of nickel to iron is 1:(0.1-0.5). The water electrolysis oxygen evolution catalyst is hollow spherical and has a porous structure on the surface, and the catalyst has a large specific surface area and high catalytic activity.

[0005] However, how to improve the electrolysis efficiency of existing alkaline water electrolysis membrane electrodes with catalysts remains an urgent problem to be solved. Summary of the invention

[0006] The purpose of the present invention is to improve the electrolysis efficiency of alkaline water electrolysis membrane electrodes.

[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a conductive membrane electrode, comprising an anode catalyst layer and a cathode catalyst layer, wherein the gaps between the oxygen evolution catalyst in the anode catalyst layer and / or the hydrogen evolution catalyst in the cathode catalyst layer are filled with semiconductor nanoparticles, and a PN heterojunction is formed between the semiconductor nanoparticles and can be electrocatalytically conductive with the oxygen evolution catalyst or the hydrogen evolution catalyst.

[0008] Optionally, the semiconductor nanoparticles are selected from one or more of metal oxides, metal selenides, metal sulfides and tellurides; and the mass ratio of the oxygen evolution catalyst and / or hydrogen evolution catalyst to the semiconductor nanoparticles is 1:(0.05-0.5).

[0009] Preferably, the mass ratio of the oxygen evolution catalyst and / or hydrogen evolution catalyst to the semiconductor nanoparticles is 1:(0.05-0.2).

[0010] Optionally, the semiconductor nanoparticles include P-type semiconductor nanoparticles and N-type semiconductor nanoparticles, and the molar ratio of the P-type semiconductor nanoparticles to the N-type semiconductor nanoparticles is (0.5-1.5):1.

[0011] Optionally, the N-type semiconductor nanoparticles are selected from one or more of V2O5, V3O8, WO3, MoO2, Fe3O4 and BaTiO3; the P-type semiconductor nanoparticles are selected from one or more of NiO, CoO, MnO, SnO, SnS, Sb2S3 and Bi2Te3.

[0012] Optionally, the particle size of the oxygen evolution catalyst or the hydrogen evolution catalyst is 0.05-10 μm; the particle size of the semiconductor nanoparticles is 10-50 nm.

[0013] Optionally, the thickness of the anode catalyst layer is 10-200 μm; the thickness of the cathode catalyst layer is 1-200 μm; hydrogen evolution The catalyst is selected from one or more of Fe, Co, Ni, Mo or their alloys or composite catalysts; Oxygen evolution The catalyst is selected from one or more of Fe, Co, Ni, Mo or alloys, oxides or metal salts thereof.

[0014] Preferably, the hydrogen evolution catalyst is selected from one or more of RanyNi, Ni, Co / NiS2, NiO / Ni and CoSn2; the oxygen evolution catalyst is selected from one or more of RanyNi, NiCo2O4, LaNiO3 and Ni-Co-P alloy.

[0015] A second aspect of the present invention provides a method for preparing a conductive film electrode, the method comprising:

[0016] P-type semiconductor powder and N-type semiconductor powder are mixed evenly to obtain mixed semiconductor powder; anode slurry and cathode slurry are prepared respectively, and the mixed semiconductor powder is added to the anode slurry and / or cathode slurry and dispersed evenly to obtain composite anode slurry and / or composite cathode slurry; the composite anode slurry or composite cathode slurry is coated on one side of a diaphragm, or the composite anode slurry and composite cathode slurry are coated on both sides of the diaphragm respectively, dried, hot pressed, and a conductive membrane electrode is obtained; based on the weight of the catalyst in the anode slurry or cathode slurry, the amount of the mixed semiconductor powder added is 5-50 wt%; the ratio of the thickness of the slurry coated on the anode side of the diaphragm to the thickness of the slurry coated on the cathode side is (1-10):1.

[0017] Optionally, the preparation method of the anode slurry or cathode slurry includes: mixing the anode catalyst or cathode catalyst with a thickener, a dispersant, a binder and a solvent and stirring them evenly to obtain the anode slurry or cathode slurry; the mass ratio of the anode catalyst or cathode catalyst to the binder is 1:(0.2-10); the mass ratio of the anode catalyst or cathode catalyst to the dispersant is (10-1000):1; the mass ratio of the anode catalyst or cathode catalyst to the thickener is (10-1000):1; the mass ratio of the anode catalyst or cathode catalyst to the solvent is 1:(0.2-5).

[0018] Optionally, the binder is selected from one or more of perfluorosulfonic acid resin, polytetrafluoroethylene resin, polyethersulfone and fluororesin;

[0019] The dispersant is a phosphate dispersant or an acrylic dispersant, preferably one or more of sodium hexametaphosphate, potassium tripolyphosphate, acrylate, acrylic acid copolymer homopolymer and acrylic acid amine salt;

[0020] The thickener is selected from one or more of cellulose ether thickeners, polyurethane thickeners and modified polyurea thickeners;

[0021] The solvent is selected from one or more of water, methanol, ethanol, isopropanol, propylene glycol and butanol; preferably one or more of water, ethanol and isopropanol;

[0022] The diaphragm is selected from one or more of a polyphenylene sulfide (PPS) diaphragm, a polyetheretherketone fiber diaphragm and a polysulfone fiber diaphragm;

[0023] The ratio of the thickness of the slurry coated on the anode side of the diaphragm to the thickness of the slurry coated on the cathode side is (1-10):1.

[0024] Optionally, the drying is carried out under vacuum conditions, the drying temperature is 50-150° C., and the drying time is 1-3 hours; the hot pressing temperature is 80-200° C., and the hot pressing pressure is 20-100 bar.

[0025] A third aspect of the present invention provides an electrolytic cell equipped with the conductive membrane electrode according to the first aspect of the present invention.

[0026] Through the above technical scheme, the gaps between the catalysts in the conductive membrane electrode of the present invention are filled with semiconductor nanoparticles, the semiconductor nanoparticles are in contact to form a PN heterojunction, and can be electrically conductive with the catalyst, thereby improving the utilization rate of the catalyst and the overall catalytic efficiency of the catalyst, thereby improving the electrolysis efficiency of the alkaline water membrane electrode.

[0027] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0029] Figure 1 It is a schematic structural diagram of a conductive film electrode according to an embodiment of the present invention.

[0030] Figure 2 It is a schematic diagram of a catalyst layer in a conductive membrane electrode according to an embodiment of the present invention. DETAILED DESCRIPTION

[0031] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0032] The inventors found that the electrolysis efficiency of the existing alkaline water electrolysis membrane electrode is not high. On the one hand, this is because the alkaline water electrolysis catalyst has poor conductivity and the binder is non-conductive, resulting in low catalyst utilization. On the other hand, the catalyst coated with the binder cannot play a catalytic role, the electrolytic cell has high ohmic resistance, and the membrane electrode catalytic efficiency is low. Therefore, an improved alkaline water electrolysis membrane electrode is proposed.

[0033] A first aspect of the present invention provides a conductive membrane electrode, comprising an anode catalyst layer and a cathode catalyst layer, wherein the gaps between the oxygen evolution catalyst in the anode catalyst layer and / or the hydrogen evolution catalyst in the cathode catalyst layer are filled with semiconductor nanoparticles, and the semiconductor nanoparticles form a PN heterojunction and can be electrocatalytically conductive with the oxygen evolution catalyst or the hydrogen evolution catalyst.

[0034] In the present invention, the PN junction is a transition zone formed by the interface between an N-type semiconductor and a P-type semiconductor, that is, the PN junction refers to the contact surface between a P-type semiconductor and an N-type semiconductor. N-type semiconductors are prone to generate free electrons, and P-type semiconductors are prone to generate holes, i.e., positive electricity. Direct contact between the two can generate a built-in electric field. Under a forward voltage, electrons move from an N-type semiconductor to a P-type semiconductor, and holes move from a P-type semiconductor to an N-type semiconductor, thereby generating current to achieve unidirectional conduction.

[0035] like Figure 1 As shown, the conductive membrane electrode structure of the present invention comprises a diaphragm 20 and an anode catalyst layer 10 and a cathode catalyst layer 30 respectively arranged on both sides of the diaphragm. The catalyst layer is prepared by slurrying the catalyst and coating it on the diaphragm, followed by drying and hot pressing.

[0036] Figure 2 Schematic diagram of the catalyst layer of the conductive membrane electrode of the present invention, the catalyst layer may be an anode catalyst layer or a cathode catalyst layer, or both the anode catalyst layer and the cathode catalyst layer may be schematically shown. Figure 2 As an example of the anode catalyst layer, refer to Figure 2 The semiconductor nanoparticles 12 are filled in the gaps between the catalysts 11, and a PN heterojunction is formed between the semiconductor nanoparticles 12. Therefore, when the conductive film electrode is powered on, the semiconductor nanoparticles 12 can be electrically catalytically connected with the catalyst 11.

[0037] Through the above technical solution, the semiconductor nanoparticles are fully in contact with each other to form a PN heterojunction, and can be electrically conductive with the oxygen evolution catalyst or the hydrogen evolution catalyst through electrocatalytic electron conduction. The catalyst coated with the binder can also fully undergo a catalytic reaction, the utilization rate of the catalyst is improved, the catalytic reaction is sufficient, the ohmic resistance is reduced, the electrolysis efficiency of the membrane electrode is improved, and the catalytic performance of the low-cost catalyst for alkaline water electrolysis is close to that of the precious metal catalyst.

[0038] The semiconductor nanoparticles are selected from one or more of metal oxides, metal selenides, metal sulfides and tellurides; the mass ratio of the oxygen evolution catalyst and / or the hydrogen evolution catalyst to the semiconductor nanoparticles is 1:(0.05-0.5); since the oxygen evolution catalyst and / or the hydrogen evolution catalyst are filled with semiconductor nanopowders in the above ratio, the oxygen evolution catalyst or the hydrogen evolution catalyst covered by the binder can be electrocatalytically conducted, and the utilization rate of the catalyst is improved without affecting the catalytic performance of the catalyst.

[0039] According to the present invention, metal oxides mainly refer to transition metal elements or oxides of metal elements; metal selenides mainly refer to transition metal elements or selenides of metal elements; metal sulfides mainly refer to sulfides of Group II-VI elements and transition metal elements; tellurides mainly refer to tellurides of transition metals or metal tellurides.

[0040] Wherein, the mass ratio of the oxygen evolution catalyst and / or hydrogen evolution catalyst to the semiconductor nanoparticles is 1:(0.05-0.2);

[0041] The semiconductor nanoparticles include P-type semiconductor nanoparticles and N-type semiconductor nanoparticles, and the molar ratio of the P-type semiconductor nanoparticles to the N-type semiconductor nanoparticles is (0.5-1.5):1.

[0042] Optionally, the N-type semiconductor nanoparticles are selected from one or more of V2O5, V3O8, WO3, MoO2, Fe3O4 and BaTiO3; the P-type semiconductor nanoparticles are selected from one or more of NiO, CoO, MnO, SnO, SnS, Sb2S3 and Bi2Te3.

[0043] In the present invention, the particle size of the oxygen evolution catalyst or hydrogen evolution catalyst is 0.05-10 μm, and the particle size of the semiconductor nanoparticles is 10-50 nm, so that the semiconductor nanoparticles can be easily distributed around the oxygen evolution catalyst and / or hydrogen evolution catalyst.

[0044] Wherein, the thickness of the anode catalyst layer is 10-200μm; the thickness of the cathode catalyst layer is 1-200μm. Preferably, the thickness of the anode catalyst layer is 20-100μm, and the thickness of the cathode catalyst layer is 5-100μm. The catalyst loading of the catalyst layer is directly proportional to the thickness of the catalyst layer. Generally, the thicker the catalyst layer, the higher the catalyst loading. Although it is beneficial to improve the catalytic activity, the resistance of the catalyst layer may increase dramatically, which offsets the improved catalytic ability. The thinner the catalyst layer, although it can reduce the resistance of the catalyst layer, it is easy to cause insufficient catalytic activity of the catalyst layer.

[0045] Wherein, the hydrogen evolution catalyst is selected from one or more of Fe, Co, Ni, Mo or their alloys or composite catalysts; the oxygen evolution catalyst is selected from one or more of Fe, Co, Ni, Mo or their alloys or oxides or metal salts.

[0046] Preferably, the hydrogen evolution catalyst is selected from one or more of RanyNi, Ni, Co / NiS2, NiO / Ni and CoSn2; the oxygen evolution catalyst is selected from one or more of RanyNi, NiCo2O4, LaNiO3 and Ni-Co-P alloy.

[0047] In the present invention, if a combination of multiple catalysts is selected for the oxygen evolution catalyst and the hydrogen evolution catalyst, the ratio between the metal elements can be adjusted according to the interaction between the different catalysts to ensure the catalytic activity of the catalyst. In the present invention, the alloy of Fe, Co, Ni, and Mo refers to a binary or multi-component alloy composed of Fe, Co, Ni, and Mo.

[0048] In the present invention, the composite catalyst of Fe, Co, Ni and Mo refers to a complex composed of Fe, Co, Ni, Mo and the like, or a catalyst formed by compounding other compounds on Fe, Co, Ni and Mo.

[0049] In the present invention, the oxides of Fe, Co, Ni and Mo refer to binary or multi-component oxides composed of Fe, Co, Ni and Mo.

[0050] In the present invention, the metal acid salts of Fe, Co, Ni and Mo may specifically be ferrites, cobaltates, nickelates and molybdates.

[0051] A second aspect of the present invention provides a method for preparing a conductive film electrode, the method comprising:

[0052] P-type semiconductor powder and N-type semiconductor powder are mixed evenly to obtain mixed semiconductor powder; anode slurry and cathode slurry are prepared respectively, and the semiconductor nanopowder is added to the anode slurry and / or cathode slurry and dispersed evenly to obtain composite anode slurry and / or composite cathode slurry; the composite anode slurry or composite cathode slurry is coated on one side of the diaphragm, or the composite anode slurry and composite cathode slurry are coated on both sides of the diaphragm respectively, and dried and hot pressed to obtain a conductive film electrode;

[0053] The amount of the mixed semiconductor powder added is 0.1-40 wt % based on the weight of the catalyst in the anode slurry or the cathode slurry;

[0054] The ratio of the thickness of the slurry coated on the anode side of the diaphragm to the thickness of the slurry coated on the cathode side is (1-10):1.

[0055] In the present invention, after adding the above-mentioned mixed semiconductor powder to the anode slurry and / or cathode slurry, the mixed semiconductor powder is fully dispersed in the slurry, specifically, it can be dispersed by a homogenizer to prevent the particles in the slurry from agglomerating and thus affecting the conductivity of the catalyst and the semiconductor.

[0056] In the present invention, the anode slurry and / or cathode slurry is doped with the mixed semiconductor powder, that is, the mixed semiconductor powder is only doped in the anode slurry or the cathode slurry, or the mixed semiconductor powder is doped in both the anode slurry and the cathode slurry.

[0057] When the above-mentioned mixed semiconductor powder is doped only in the anode slurry or the cathode slurry, the slurry doped with the mixed semiconductor powder is coated on one side of the diaphragm, and the slurry without the mixed semiconductor powder is coated on the other side. In a specific embodiment, the coating method includes but is not limited to conventional coating methods such as scraping, spraying, and transfer, and other methods for uniformly dispersing the catalyst slurry on the diaphragm can also be used. The specific process is not repeated here one by one.

[0058] The method for preparing the anode slurry or cathode slurry comprises: mixing the anode catalyst or cathode catalyst with a thickener, a dispersant, a binder and a solvent and stirring the mixture uniformly to obtain the anode slurry or cathode slurry.

[0059] In a specific embodiment, the anode catalyst or cathode catalyst, thickener and part of the solvent are first mixed by ball milling to fully disperse the catalyst, and then the dispersant, binder and remaining solvent are added and stirred evenly, preferably at a low speed for 8-12 hours.

[0060] Among them, the cathode catalyst is selected from one or more of Fe, Co, Ni, Mo or their alloys or composite catalysts, preferably selected from one or more of RanyNi, Ni, Co / NiS2, NiO / Ni and CoSn2; the anode catalyst is selected from one or more of Fe, Co, Ni, Mo or their alloys or oxides or metal salts, preferably selected from one or more of RanyNi, NiCo2O4, LaNiO3 and Ni-Co-P alloy.

[0061] Wherein, the binder is selected from one or more of perfluorosulfonic acid resin, polytetrafluoroethylene resin, polyethersulfone and fluororesin;

[0062] The dispersant is a phosphate dispersant or an acrylic dispersant, preferably one or more of sodium hexametaphosphate, potassium tripolyphosphate, acrylate, acrylic acid copolymer homopolymer and acrylic acid amine salt;

[0063] The thickener is selected from one or more of cellulose ether thickeners, polyurethane thickeners and modified polyurea thickeners;

[0064] The solvent is selected from one or more of water, methanol, ethanol, isopropanol, propylene glycol and butanol; preferably one or more of water, ethanol and isopropanol;

[0065] The diaphragm is selected from one or more of a polyphenylene sulfide (PPS) diaphragm, a polyetheretherketone fiber diaphragm and a polysulfone fiber diaphragm.

[0066] In the present invention, the binder can improve the uniformity and stability of the catalyst slurry, and is preferably used in the form of a solution, and the binder is selected from one or more of a perfluorosulfonic acid resin solution, a polytetrafluoroethylene resin solution, a polyethersulfone solution, and a fluororesin dispersion. Among them, the fluororesin can be a fluorine-containing resin such as a polytrifluorochloroethylene resin, a polyvinylidene fluoride resin, and a polyvinyl fluoride resin.

[0067] In the present invention, the mass ratio of the anode catalyst or cathode catalyst to the binder is 1:(0.2-10), preferably 1:(0.5-5); the mass ratio of the anode catalyst or cathode catalyst to the dispersant is (10-1000):1, preferably (20-1000):1; the mass ratio of the anode catalyst or cathode catalyst to the thickener is (10-1000):1, preferably (20-1000):1; the mass ratio of the anode catalyst or cathode catalyst to the solvent is 1:(0.2-5), preferably 1:(0.5-5).

[0068] In the present invention, the thickness of the slurry coated on the anode side of the diaphragm is 10-200 μm, preferably 20-100 μm; the thickness of the slurry coated on the cathode side of the diaphragm is 1-200 μm, preferably 5-100 μm.

[0069] Wherein, the drying is carried out under vacuum conditions, the drying temperature is 50-150°C, preferably 50-100°C, the drying time is 1-3h, preferably 1-2h; the hot pressing temperature is 80-200°C, preferably 100-190°C, and the hot pressing pressure is 20-100bar, preferably 30-70bar.

[0070] In a specific embodiment, the method for preparing the conductive film electrode comprises:

[0071] P-type semiconductor nanopowder and N-type semiconductor nanopowder are ground and mixed evenly, so that the P-type semiconductor nanopowder and the N-type semiconductor powder are in contact with each other to form a PN junction interface, thereby obtaining a mixed semiconductor powder; respectively preparing an anode slurry and a cathode slurry of an alkaline membrane electrode, adding the mixed semiconductor powder to the anode slurry and / or the cathode slurry, and fully dispersing the mixed semiconductor powder with a homogenizer to obtain a composite anode slurry and / or a composite cathode slurry; coating the composite slurry containing the mixed semiconductor powder on one side of a diaphragm, and coating the other side with a slurry without adding the mixed semiconductor powder, or coating the composite anode slurry and the composite cathode slurry on both sides of the diaphragm, drying, and hot pressing to obtain a conductive membrane electrode;

[0072] Among them, the preparation method of anode slurry or cathode slurry includes the steps of: mixing and dispersing the anode catalyst or cathode catalyst with a thickener and part of the solvent, then adding a dispersant, a binder and the remaining solvent, and stirring evenly to obtain the anode slurry or cathode slurry; the drying is carried out under vacuum conditions, the drying temperature is 50-150°C, and the drying time is 1-3h; the hot pressing temperature is 80-200°C, and the hot pressing pressure is 20-100bar.

[0073] A third aspect of the present invention provides an electrolytic cell equipped with the conductive membrane electrode according to the first aspect of the present invention.

[0074] The present invention is further described in detail below by way of examples, but the present invention is not limited to the following examples.

[0075] Unless otherwise specified, the raw materials used in the following examples can be obtained through commercial sources.

[0076] Example 1

[0077] Example 1 A membrane electrode E1 in which a semiconductor nanopowder is doped in an anode catalyst layer is prepared. The preparation method comprises the following steps:

[0078] (1) P-type semiconductor nanopowder and N-type semiconductor nanopowder are taken in equal amounts and placed in an agate mortar and ground for 2 h until they are evenly mixed to obtain a mixed semiconductor powder; wherein the P-type semiconductor is CoO, the N-type semiconductor is V2O5, and the particle size of the mixed semiconductor powder is 10-50 nm.

[0079] (2) Preparation of catalyst layer slurry

[0080] The anode catalyst is mixed and dispersed with a thickener and part of the solvent, and then a dispersant, a binder and the remaining solvent are added, and stirred at a low speed for 10 hours to obtain an anode slurry; wherein the anode catalyst is RanyNi, the thickener is carboxymethyl cellulose, the dispersant is potassium tripolyphosphate, the binder is a perfluorosulfonic acid resin binder, the solvent is water, and the mass ratio of the anode catalyst to the thickener, the dispersant, the binder and the solvent is 1:0.001:0.001:1:0.5;

[0081] The cathode catalyst is mixed and dispersed with a thickener and part of the solvent, and then a dispersant, a binder and the remaining solvent are added, and stirred at a low speed for 10 hours to obtain a cathode slurry; wherein the cathode catalyst is RanyNi, the thickener is carboxymethyl cellulose, the dispersant is potassium tripolyphosphate, the binder is a perfluorosulfonic acid resin binder, the solvent is water, and the mass ratio of the cathode catalyst to the thickener, the dispersant, the binder and the solvent is 1:0.01:0.01:0.5:0.5;

[0082] Adding mixed semiconductor powder to the anode slurry and fully dispersing it with a homogenizer to obtain a composite anode slurry; wherein the mass ratio of the anode catalyst to the mixed semiconductor powder is 1:0.1;

[0083] (3) The composite anode slurry was sprayed on one side of the diaphragm, and the cathode slurry was sprayed on the other side. The thickness of the slurry on the anode side of the diaphragm was 50 μm, and the thickness of the slurry on the cathode side was 50 μm. After coating, it was placed in a vacuum oven for drying, and then hot pressed to prepare a conductive film electrode. The drying temperature was 100 ° C, the drying time was 2 hours, and the hot pressing temperature was 150 ° C, and the pressure was 60 bar.

[0084] Example 2

[0085] Example 2 A membrane electrode E2 in which both the anode catalyst layer and the cathode catalyst layer are doped with semiconductor nanopowder is prepared. The preparation method comprises the following steps:

[0086] (1) P-type semiconductor nanopowder and N-type semiconductor nanopowder are taken in equal amounts and placed in an agate mortar and ground for 3 h until they are evenly mixed to obtain a mixed semiconductor powder; wherein the P-type semiconductor is NiO and the N-type semiconductor is V3O8.

[0087] (2) Preparation of catalyst layer slurry

[0088] The anode catalyst is mixed and dispersed with a thickener and part of the solvent, and then a dispersant, a binder and the remaining solvent are added, and stirred at a low speed for 10 hours to obtain an anode slurry; wherein the anode catalyst is NiCo2O4, the thickener is CMC (sodium carboxymethyl cellulose), the dispersant is sodium hexametaphosphate, the binder is a perfluorosulfonic acid resin binder, and the solvent is water; the mass ratio of the anode catalyst to the thickener, the dispersant, the binder, and the solvent is 1:0.003:0.005:1.2:0.8;

[0089] The cathode catalyst is mixed and dispersed with a thickener and part of the solvent, and then a dispersant, a binder and the remaining solvent are added, and stirred at a low speed for 10 hours to obtain a cathode slurry; wherein the cathode catalyst is nano-Ni, the thickener is CMC, the dispersant is sodium hexametaphosphate, the binder is a perfluorosulfonic acid resin binder, and the solvent is water; the mass ratio of the cathode catalyst to the thickener, the dispersant, the binder, and the solvent is 1:0.03:0.03:1:0.5;

[0090] Adding mixed semiconductor powder to the anode slurry and cathode slurry respectively, and fully dispersing them with a homogenizer to obtain composite anode slurry and composite cathode slurry; wherein the mass ratio of the anode catalyst to the mixed semiconductor powder is 1:0.1, and the mass ratio of the cathode catalyst to the mixed semiconductor powder is 1:0.05;

[0091] (3) The composite anode slurry was sprayed on one side of the diaphragm, and the composite cathode slurry was sprayed on the other side. The thickness of the slurry on the anode side of the diaphragm was 60 μm, and the thickness of the slurry on the cathode side was 30 μm. After coating, it was placed in a vacuum oven for drying, and then hot pressed to prepare a conductive film electrode. The drying temperature was 100 ° C, the drying time was 2 hours, and the hot pressing temperature was 150 ° C, and the pressure was 60 bar.

[0092] Example 3

[0093] Example 3 A membrane electrode E3 in which the anode catalyst layer is doped with semiconductor nanopowder is prepared in the same manner as in Example 1. The difference from Example 1 is that:

[0094] In step (1), the P-type semiconductor is Bi2Te3 and the N-type semiconductor is BaTiO3;

[0095] In step (2), the mass ratio of the anode catalyst to the thickener, dispersant, binder, and solvent is 1:0.04:0.01:1.5:1, the mass ratio of the cathode catalyst to the thickener, dispersant, binder, and solvent is 1:0.01:0.05:1:1; and the mass ratio of the anode catalyst to the mixed semiconductor powder is 1:0.08.

[0096] Example 4

[0097] Example 5 A membrane electrode E4 in which the anode catalyst layer is doped with semiconductor nanopowder is prepared in the same manner as in Example 1. The difference from Example 1 is that:

[0098] In step (1), the P-type semiconductor is Sb2S3 and the N-type semiconductor is Fe3O4;

[0099] In step (2), the mass ratio of the anode catalyst to the thickener, dispersant, binder, and solvent is 1:0.005:0.03:0.6:1, the mass ratio of the cathode catalyst to the thickener, dispersant, binder, and solvent is 1:0.01:0.05:0.4:0.5; and the mass ratio of the anode catalyst to the mixed semiconductor powder is 1:0.05.

[0100] Example 5

[0101] Example 5 A membrane electrode E5 in which the anode catalyst layer is doped with semiconductor nanopowder is prepared in the same manner as in Example 1. The difference from Example 1 is that:

[0102] In step (2), the mass ratio of the anode catalyst to the mixed semiconductor powder is 1:0.15;

[0103] In step (3), the thickness of the slurry coated on the anode side of the separator is 100 μm, and the thickness of the slurry coated on the cathode side is 10 μm.

[0104] Example 6

[0105] Example 6 A membrane electrode E6 in which the anode catalyst layer is doped with semiconductor nanopowder is prepared in the same manner as in Example 1. The difference from Example 1 is that:

[0106] In step (2), the anode catalyst is LaNiO3, the thickener is CMC, the dispersant is acrylic acid amine salt, the binder is polyether sulfone, and the solvent is water; the cathode catalyst is Co / NiS2, the thickener is CMC, the dispersant is acrylic acid amine salt, the binder is polyether sulfone, and the solvent is water.

[0107] Example 7

[0108] Example 7 A membrane electrode E7 in which a semiconductor nanopowder is doped in a cathode catalyst layer is prepared in the same manner as in Example 1. The difference from Example 1 is that:

[0109] In step (2), no mixed semiconductor powder is added to the anode slurry; the mixed semiconductor powder is added to the cathode slurry and fully dispersed by a homogenizer to obtain a composite cathode slurry; the mass ratio of the cathode catalyst to the mixed semiconductor powder is 1:0.1;

[0110] In step (3), the composite cathode slurry is applied to one side of the diaphragm with a spray gun, and the anode slurry is applied to the other side. The thickness of the slurry applied to the anode side of the diaphragm is 50 μm, and the thickness of the slurry applied to the cathode side is 50 μm.

[0111] Comparative Example 1

[0112] Comparative Example 1 prepares a membrane electrode D1 not doped with semiconductor nanopowder, which is carried out in the same manner as the method for preparing the membrane electrode in Example 1, except that:

[0113] In step (2), the mass ratio of the anode catalyst to the thickener, dispersant, binder, and solvent is 1:0.01:0.01:1:1, and no mixed semiconductor powder is added to the anode slurry;

[0114] The mass ratio of cathode catalyst to thickener, dispersant, binder and solvent is 1:0.05:0.01:1:0.5.

[0115] Comparative Example 2

[0116] Comparative Example 2 prepares a membrane electrode D2 in which the anode catalyst layer is doped with semiconductor nanopowder, which is carried out in the same manner as the method for preparing the membrane electrode in Example 1, and the difference from Example 1 is that:

[0117] In step (2), the mass ratio of the anode catalyst to the mixed semiconductor powder is 1:0.01; the thickness of the slurry coated on the anode side of the diaphragm is 50 μm, and the thickness of the slurry coated on the cathode side is 20 μm.

[0118] Comparative Example 3

[0119] Comparative Example 3 prepared a membrane electrode D3 in which the anode catalyst layer was doped with semiconductor nanopowder, which was carried out in the same manner as the method for preparing the membrane electrode in Example 1, and the difference from Example 1 was that:

[0120] The particle size of the mixed semiconductor powder in step (1) is greater than 50 nm;

[0121] In step (2), the mass ratio of the anode catalyst to the thickener, dispersant, binder and solvent is 1:0.05:0.01:1:0.5.

[0122] Performance Testing

[0123] (1) Powder conductivity test

[0124] The powder conductivity test method is to mix the anode catalyst or cathode catalyst in Examples 1-7 and Comparative Examples 1-3 with the corresponding semiconductor powder, and then take 3-5g of the mixed powder and press it into a tablet with a diameter of 3cm on a tablet press, with a pressure of 30-50mPa and keep the pressure for 1-5 minutes. Then, the conductivity of the tablet is tested with a four-probe conductivity meter. The test results are shown in Table 1.

[0125] Table 1

[0126]

[0127] It can be seen from the test results that by adding semiconductor powder capable of forming a PN heterojunction as a conductive agent to the anode catalyst or the cathode catalyst, the conductivity of the mixed powder is significantly enhanced.

[0128] (2) Stack test

[0129] The 400 cm prepared in Examples 1-7 and Comparative Examples 1-3 2 The membrane electrode was placed at 400 cm 2 The single-chamber electrolysis fixture was used for testing, and a constant current electrolysis was performed with an electrolysis current of 160A and a current density of 0.4A / cm 2 The tested voltages are shown in Table 2.

[0130] Table 2

[0131]

[0132] From the test results, it can be seen that Examples 1-7 have a2 When electrolyzed at a current density of 1, the decomposition voltage is significantly lower than that of the comparative example 1 in which no semiconductor powder conductive agent is added, indicating that the addition of semiconductor powder capable of forming a PN heterojunction improves the utilization rate of the catalyst and the electrolysis efficiency.

[0133] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0134] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0135] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A conductive membrane electrode for producing hydrogen by alkaline water electrolysis, comprising an anode catalyst layer and a cathode catalyst layer, characterized in that: The gaps between the oxygen evolution catalyst in the anode catalyst layer and / or the hydrogen evolution catalyst in the cathode catalyst layer are filled with semiconductor nanoparticles, and the semiconductor nanoparticles form a PN heterojunction and can be electrically catalytically connected with the oxygen evolution catalyst or the hydrogen evolution catalyst; The hydrogen evolution catalyst is selected from one or more of Fe, Co, Ni, Mo or their alloys or composite catalysts; the oxygen evolution catalyst is selected from one or more of Fe, Co, Ni, Mo or their alloys or oxides or metal salts; The semiconductor nanoparticles include P-type semiconductor nanoparticles and N-type semiconductor nanoparticles; the N-type semiconductor nanoparticles are selected from one or more of V2O5, V3O8, WO3, MoO2, Fe3O4 and BaTiO3; the P-type semiconductor nanoparticles are selected from one or more of NiO, CoO, MnO, SnO, SnS, Sb2S3 and Bi2Te3.

2. The conductive film electrode according to claim 1, wherein: The mass ratio of the oxygen evolution catalyst and / or hydrogen evolution catalyst to the semiconductor nanoparticles is 1:(0.05-0.5).

3. The conductive film electrode according to claim 2, wherein: The mass ratio of the oxygen evolution catalyst and / or hydrogen evolution catalyst to the semiconductor nanoparticles is 1:(0.05-0.2); The molar ratio of the P-type semiconductor nanoparticles to the N-type semiconductor nanoparticles is (0.5-1.5):

1.

4. The conductive film electrode according to claim 1, wherein: The particle size of the oxygen evolution catalyst or hydrogen evolution catalyst is 0.05-10 μm; the particle size of the semiconductor nanoparticles is 10-50 nm.

5. The conductive film electrode according to claim 1, wherein: The thickness of the anode catalyst layer is 10-200 μm; the thickness of the cathode catalyst layer is 1-200 μm.

6. The conductive film electrode according to claim 1, wherein: The hydrogen evolution catalyst is selected from one or more of RanyNi, Ni, Co / NiS2, NiO / Ni and CoSn2; The oxygen evolution catalyst is selected from one or more of RanyNi, NiCo2O4, LaNiO3 and Ni-Co-P alloy.

7. A method for preparing a conductive film electrode according to any one of claims 1 to 6, characterized in that: The method includes: Mixing P-type semiconductor powder and N-type semiconductor powder evenly to obtain mixed semiconductor powder; Prepare anode slurry and cathode slurry respectively, add the mixed semiconductor powder into the anode slurry and / or cathode slurry and disperse evenly to obtain composite anode slurry and / or composite cathode slurry; Applying the composite anode slurry or composite cathode slurry on one side of the diaphragm, or applying the composite anode slurry and composite cathode slurry on both sides of the diaphragm respectively, drying and hot pressing to obtain a conductive film electrode; The amount of the mixed semiconductor powder added is 5-50 wt% based on the weight of the catalyst in the anode slurry or the cathode slurry; The ratio of the thickness of the slurry coated on the anode side of the diaphragm to the thickness of the slurry coated on the cathode side is (1-10):

1.

8. The method according to claim 7, wherein: The method for preparing the anode slurry or cathode slurry comprises: mixing the anode catalyst or cathode catalyst with a thickener, a dispersant, a binder and a solvent and stirring them uniformly to obtain the anode slurry or cathode slurry; The mass ratio of the anode catalyst or cathode catalyst to the binder is 1:(0.2-10); The mass ratio of the anode catalyst or cathode catalyst to the dispersant is (10-1000): 1; The mass ratio of the anode catalyst or cathode catalyst to the thickener is (10-1000): 1; The mass ratio of the anode catalyst or cathode catalyst to the solvent is 1:(0.2-5).

9. The method according to claim 8, wherein: The binder is selected from one or more of perfluorosulfonic acid resin, polytetrafluoroethylene resin, polyethersulfone and fluororesin; The dispersant is a phosphate dispersant or an acrylic dispersant; The thickener is selected from one or more of cellulose ether thickeners, polyurethane thickeners and modified polyurea thickeners; The solvent is selected from one or more of water, methanol, ethanol, isopropanol, propylene glycol and butanol; The diaphragm is selected from one or more of a polyphenylene sulfide (PPS) diaphragm, a polyetheretherketone fiber diaphragm and a polysulfone fiber diaphragm.

10. The method according to claim 9, wherein: The dispersant is selected from one or more of sodium hexametaphosphate, potassium tripolyphosphate, acrylate, acrylic acid copolymer homopolymer and acrylic acid amine salt; The solvent is selected from one or more of water, ethanol and isopropanol.

11. The method according to claim 7, wherein: The drying is carried out under vacuum conditions, the drying temperature is 50-150° C., and the drying time is 1-3 hours; the hot pressing temperature is 80-200° C., and the hot pressing pressure is 20-100 bar.

12. An electrolytic cell, characterized in that: A conductive film electrode as described in any one of claims 1 to 6 is installed.

Citation Information

Patent Citations

  • Alkaline water electrolysis method and anode for alkaline water electrolysis

    CN113544313B

  • Water electrolysis oxygen evolution catalyst, preparation method and alkaline water electrolysis hydrogen production device

    CN115976564A

  • Membrane electrode for water electrolysis and preparation method thereof

    CN101781769A

  • Fuel cell catalyst slurry, electrode and preparation methods of two

    CN110534761A